2015
DOI: 10.1007/s00404-015-3766-2
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA inhibits the proliferation, migration and invasion of ectopic endometrial stromal cells of adenomyosis via 14-3-3ζ downregulation

Abstract: TSIIA could be a promising novel therapeutic agent for adenomyosis, via inducing cell apoptosis, inhibiting cell viability, migration and invasion in EESCs. Furthermore, the effects of cell viability, migration and invasion were mediated in 14-3-3ζ-dependent manner while that of cell apoptosis was mediated in 14-3-3ζ-independent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…EESCs (EESC1, EESC2 and EESC3, respectively) were isolated and characterized as described previously (19)(20)(21). In brief, the tissues were washed twice with sterile PBS under aseptic conditions, minced into small pieces, digested by incubation with Dulbecco's modified Eagle's medium (DMEM)/F12 (Hyclone; GE Healthcare Life Sciences, South Logan, UT, USA) supplemented with 1 mg/ml collagenase (Serva Electrophoresis GmbH, Heidelberg, Germany) and 10% fetal bovine serum (FBS; Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA) for 2 h at 37˚C and subsequently filtrated with a 70-mm nylon cell strainer.…”
Section: Subjects and Specimensmentioning
confidence: 99%
“…EESCs (EESC1, EESC2 and EESC3, respectively) were isolated and characterized as described previously (19)(20)(21). In brief, the tissues were washed twice with sterile PBS under aseptic conditions, minced into small pieces, digested by incubation with Dulbecco's modified Eagle's medium (DMEM)/F12 (Hyclone; GE Healthcare Life Sciences, South Logan, UT, USA) supplemented with 1 mg/ml collagenase (Serva Electrophoresis GmbH, Heidelberg, Germany) and 10% fetal bovine serum (FBS; Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA) for 2 h at 37˚C and subsequently filtrated with a 70-mm nylon cell strainer.…”
Section: Subjects and Specimensmentioning
confidence: 99%
“…The primary EESCs were stained positive with anti-vimentin, a specific marker of stromal cells [5, 26], while they were stained negative with anti-cytokeratin by immunocytochemistry, a specific molecular marker for epithelial cells (Figure 1). The purity of isolated EESCs was >95% and cells between passages 4 to 12 were adopted in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2 endometrial samples (35- and 42-year-old women) undergoing surgical resection were recruited and the ectopic endometrial tissues were minced into small pieces and incubated with 1 mg/mL type IV collagenase dissolved in complete culture medium for 2 hours at 37°C; the resultant digest was filtrated and centrifuged at 2,000 rpm for 10 minutes; the obtained pellets were collected and grown in complete culture medium, as described previously [5, 25]. The isolated primary EESCs were cultured in DMEM/F12 with 10% FBS, containing 100 IU/mL penicillin and 50 mg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior study showed that 14-3-3ζ impaired cell proliferation in human ectopic endometrial in vitro [21]. 14-3-3ζ dysregulates BH3-only protein and leads to a lower level of Bax activation resulting in apoptosis suppression [2223].…”
Section: Discussionmentioning
confidence: 99%